Acerca del emprendimiento en Colombia (2012)
This article is a reflection not derived from research. It includes some of the concerns of the author around entrepreneurship and as a teacher who is responsible for an academic space related to that topic.The concern is associated with the need of thinking about entrepreneurship, in a way that the topic goes beyond the mechanical topic of drawing up a business planwithout understanding that there are some elements of the context that help or hinder the development of entrepreneurship. This should lead to understanding that entrepreneurship should be a properly designed and not a random process.